2014
DOI: 10.1007/s10995-014-1432-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Health Literacy Progression Among Rural Perinatal Women

Abstract: This research examined changes in maternal health literacy progression among 106 low income, high risk, rural perinatal African American and White women who received home visits by Registered Nurse Case Managers through the Enterprise Community Healthy Start Program. Maternal health literacy progression would enable women to better address intermediate factors in their lives that impacted birth outcomes, and ultimately infant mortality (Lu and Halfon in Mater Child Health J 7(1):13–30, 2003; Sharma et al. in J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 37 publications
1
36
0
4
Order By: Relevance
“…This has not been achieved by information improvement initiatives in child health [8]. Further, previous LSP studies showed reductions in disparities related to age [30] and mental health [16,32].…”
Section: Promoting Mhl Reduces Disparitiesmentioning
confidence: 95%
See 4 more Smart Citations
“…This has not been achieved by information improvement initiatives in child health [8]. Further, previous LSP studies showed reductions in disparities related to age [30] and mental health [16,32].…”
Section: Promoting Mhl Reduces Disparitiesmentioning
confidence: 95%
“…Mobley and colleagues [16] found that rural mothers with low MHL scores had problems with housing and transportation. This finding suggested that the social determinants of health (SDoH) might be significant factors in MHL.…”
Section: Strong Relationships Among Social Determinants Of Health Andmentioning
confidence: 99%
See 3 more Smart Citations